Data on taxonomic annotation and diversity of 18S rRNA gene amplicon libraries derived from high throughput sequencing - Takafumi Kataoka; Ryuji Kondo (Data in Brief, 2019)
This Data in Brief article is a supporting information for the research article entitled “Protistan community composition in anoxic sediments from three salinity-disparate Japanese lakes” by Kataoka and Kondo (2019) [1]. Summary of 18S rRNA gene sequences originated from anoxic sediment of three lakes in two seasons using high throughput sequencing techniques (MiSeq, Illumina) was shown in this data article. Supergroup-level taxonomy was compared between the SILVA search for SILVA database and BLASTn search for the PR2 database. Alpha diversity was calculated in each sample, and beta-diversity was calculated among the six amplicon libraries. Partial sequence length between the primer set of 574*f and 1132R Hugerth et al., 2015 was compared between the forward read and the combined read. Keywords: Protists, 18S rRNA gene, High throughput sequencing (HTS), MiSeq, V4–V5 hypervariable region